2018
DOI: 10.1016/j.bcp.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacyl-tRNA synthetases, therapeutic targets for infectious diseases

Abstract: Despite remarkable advances in medical science, infection-associated diseases remain among the leading causes of death worldwide. There is a great deal of interest and concern at the rate at which new pathogens are emerging and causing significant human health problems. Expanding our understanding of how cells regulate signaling networks to defend against invaders and retain cell homeostasis will reveal promising strategies against infection. It has taken scientists decades to appreciate that eukaryotic aminoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 159 publications
1
46
0
Order By: Relevance
“…Of note, murine Jo-1 induced autoreactive B and T cells targeting its own epitopes, and the epitope spreading occurred uniformly 8 weeks after the single immunization, suggesting that autoantibody Jo-1 was able to drive a sustained immune response. When PBMCs and bronchoalveolar lavage fluid (BALF) cells from ASSD patients were stimulated with HisRS or a HisRS-derived peptide (HisRS [11][12][13][14][15][16][17][18][19][20][21][22][23] ), the expression of CD40L in CD4 + T cells from the corresponding compartments was upregulated 78 . Compared with PBMCs, BALF CD4 + T cells showed a remarkable Th1 phenotype after stimulation, such as the production of more IFN-γ and IL-2, indicating the presence of HisRS-specific CD4 + T cells in the blood and lung of patients with ASSD.…”
Section: Arss and Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, murine Jo-1 induced autoreactive B and T cells targeting its own epitopes, and the epitope spreading occurred uniformly 8 weeks after the single immunization, suggesting that autoantibody Jo-1 was able to drive a sustained immune response. When PBMCs and bronchoalveolar lavage fluid (BALF) cells from ASSD patients were stimulated with HisRS or a HisRS-derived peptide (HisRS [11][12][13][14][15][16][17][18][19][20][21][22][23] ), the expression of CD40L in CD4 + T cells from the corresponding compartments was upregulated 78 . Compared with PBMCs, BALF CD4 + T cells showed a remarkable Th1 phenotype after stimulation, such as the production of more IFN-γ and IL-2, indicating the presence of HisRS-specific CD4 + T cells in the blood and lung of patients with ASSD.…”
Section: Arss and Autoimmune Diseasesmentioning
confidence: 99%
“…For example, seryl-tRNA synthetase (SerRS) could bind to transcription factor Yin Yang 1 (YY1) to form a SerRS/YY1 complex, which interacted with distal cis-regulatory elements and then negatively regulated vascular endothelial cell growth factor A transcription during angiogenesis 10 . Furthermore, ARSs are emerging as multifaceted molecules participating in immune regulation and immune diseases [11][12][13] . It has been found that the pathogenic variants in lysyl-tRNA synthetase (KARS) cause a progressive leukodystrophy, and the patients exhibit severe phenotypes including developmental delay or arrest, deafness, and immunological abnormalities 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent discoveries that human cytosolic aaRSs and fragments thereof are involved in multiple signaling pathways and linked to numerous diseases (79 -83), ranging from cancer to Charcot-Marie-Tooth disease, strengthen this view. These enzymes have been found to act as procytokines (84,85) and partners in pathways, including tumorigenesis, immune response, and inflammation (81,82,86). Given this functional expansion among their cytosolic homologs, it is likely that similar noncanonical functions have also evolved in the mt-aaRSs.…”
Section: Toward the Origins Of Tissue Specificitymentioning
confidence: 99%
“…They play unique regulatory roles in cellular signaling pathways (22,130), and some ARSs are even secreted and act as cytokines and chemokines (131,132). The roles that ARSs play in response to viral infection and the immune response make them potential therapeutic targets and diagnostic biomarkers (133). Interestingly, many ARSs have been identified in multi-omic studies focusing on retroviral replication.…”
Section: Multi-omic Studies Suggest Additional Potential Roles For Ammentioning
confidence: 99%